Evaluation of Potential Probiotic Properties of a Strain of Lactobacillus plantarum for Shrimp Farming: From Beneficial Functions to Safety Assessment - Wei, Cong; Luo, Kai; Wang, Mingyang; Li, Yongmei; Pan, Miaojun; Xie, Yumeng; Qin, Guangcai; Liu, Yijun; Li, Li; Liu, Qingbing; Tian, Xiangli (Frontiers in Microbiology, 2022)
In recent years the safety of probiotics has received increasing attention due to the possible transfer and spread of virulence factors (VFs) and antibiotic resistance genes (ARGs) among microorganisms. The safety of a strain of Lactobacillus plantarum named W2 was evaluated in phenotype and genotype in the present study. Its probiotic properties were also evaluated both in vivo and in vitro, including adherence properties, antibacterial properties and beneficial effects on the growth and immunity of Pacific white shrimp, Penaeus vannamei. Hemolysis tests, antibiotic resistance tests and whole genome sequence analysis showed that W2 had no significant virulence effects and did not carry high virulence factors. W2 was found to be sensitive to chloramphenicol, clindamycin, gentamicin, kanamycin and tetracycline, and to be resistant to ampicillin and erythromycin. Most ARGs have no transfer risk and a few have transfer risk but no significant enrichment in human-associated environments. The autoaggregation of W2 was 82.6% and the hydrophobicity was 81.0%. Coaggregation rate with Vibrio parahaemolyticus (24.9%) was significantly higher than Vibrio’s autoaggregation rate (17.8%). This suggested that W2 had adhesion potential to mucosal/intestinal surfaces and was able to attenuate the adherence of V. parahaemolyticus. In addition, several adhesion-related protein genes, including 1 S-layer protein, 1 collagen-binding protein and 9 mucus-binding proteins were identified in the W2 genome. W2 had efficiently antagonistic activity against 7 aquatic pathogenic strains. Antagonistic components analysis indicated that active antibacterial substances might be organic acids. W2 can significantly promote the growth of shrimp when supplemented with 1 × 1010 cfu/kg live cells. Levels of 7 serological immune indicators and expression levels of 12 hepatopancreatic immune-related genes were up-regulated, and the mortality of shrimp exposed to V. parahaemolyticus was significantly reduced. Based on the above, L. plantarum W2 can be applied safely as a potential probiotic to enhance the growth performance, immunity capacity and disease resistance of P. vannamei.